Salinity stress effect on biochemical changes in leaves of rice genotypes differing in salt tolerance - T.S. Roy, M. Hasanuzzaman, A.K. Bhadra, M.A. Razzaque, N.M. Talukder (Recent Research in Science and Technology, 2009)
The impact of salinity stress on biochemical changes of salt tolerant genotypes PVSB9, PVSB19, PNR381, PNR519, Iratom24 and salt sensitive genotype NS15 along with one standard check salt tolerant rice cultivar Pokkali were assessed in two factors [7 rice genotypes in combination with 5 levels of salinity (0, 3, 6, 9 and 12 dS m-1)] in pot culture. The biochemical aspects studied include chlorophyll, free amino acids and soluble proteins of the selected rice genotypes in view to evaluate their response at different salinity levels. The results of biochemical changes indicated that salinity seriously affected the biosynthesis of leaf chlorophyll of all the selected genotypes at different days after transplanting (DAT). At 35, 65 and 75 DATs, chlorophyll a and chlorophyll a/b ratio increased with increase in salinity levels but total chlorophyll and chlorophyll b decreased with increasing the levels of salinity. The soluble protein and free amino acids content in leaves of seven selected rice genotypes increased significantly with increase in salinity levels at 35 DAT but at 60 and 75 DAT, this increasing pattern continued up to 6 and 9 dSm-1, respectively.Ã‚Â 